GENDER AND INVESTMENT BEHAVIOR: A REVIEW AND BIBLIOMETRIC ANALYSIS - Rina Suprina; Ikin Solikin; Budi Supriatono Purnomo; Nurbaeti Nurbaeti (JPIM (Jurnal Penelitian Ilmu Manajemen), 2023)
The effect of gender differences on investment behavior is a research topic that needs to be explored to understand the phenomena. This paper is to review the literature on gender and investment behavior, as well as their influence on other dimensions. The Publish or Perish software was used to acquire literature data, and the Google Scholar database was chosen. The term used for the title is "gender investment." The initial search yielded 213 publications published between 2016 and 2021. Then, 112 articles were selected from the 213 literatures that were chosen. Using the Mendeley reference manager and the Publish or Perish software, information on the most cited articles was compiled. In addition, the 112 references were processed with the VOS Viewer to generate cluster data containing the items that appear in each cluster. Also demonstrated were the overlay visualization, density visualization, and author network connected with keywords. This study gives an overview of gender issues in investment behavior for future research.